Ergonomic risks in the everyday of nursing professionals in brazilian hospitals (Research, Society and Development, 2021)
The objective was to identify the most frequent causes and threats to nursing professionals in the hospital sector, with regard to occupational health risk. This is a narrative review of the literature, the search took place in June/2019, and digital materials were evaluated in the database of the Occupational Safety and Health Observatory, such as: documents from the Ministry of Economy, Secretary and Inspection of work and a document from the Ministry of Health. 10 studies related to ergonomics in nursing professionals were also selected. Analysis of the materials show data related to the Geographical Distribution of Work Accident Communications; Estimate of underreporting of accidents at work; Economic sectors with higher numbers of notifications; Occupations within the hospital sector; Social security expenses-sickness allowance for work accidents; Most frequent injuries; Parts of the body most frequently affected; Parts of the body most frequently affected by physical exertion; and, Removal from the work environment according to the International Classification of Diseases. It was identified that approximately 60% of cases of ergonomic accidents within the hospital are suffered by nursing professionals. As for the most frequent causes of absence of professionals from the hospital environment, musculoskeletal and connective tissue injuries stood out, followed by fractures, mental and behavioral diseases, as well as dislocations. As for the most frequently affected parts of the body, the fingers stood out. Thus, greater emphasis is needed on sensitizing managers and workers about occupational hazards and their consequences, with a view to reducing exposure to risks and possible damage to health.